Analysis of Informal Debt Relations and Social Capital in the Buwuh Tradition in Lowokwaru Sub District of Malang City - Asrathul Humaira; Fitanto, Bahtiar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2026)
The buwuh tradition, a Javanese socio-cultural practice rooted in values of mutual cooperation and solidarity, is increasingly challenged by social and economic changes in urban communities, raising concerns about shifts in its original meaning and function. This study aims to examine the transformation of the meaning of the buwuh tradition, its impacts on socio-economic relationships within the community, and the role of social capital in sustaining the tradition while also generating potential functional distortions. This research employs a qualitative approach using a descriptive ethnographic method and was conducted in Lowokwaru Sub District. A total of 41 informants were selected through purposive sampling and snowball sampling techniques. Data were collected through structured interviews, observation, documentation, and literature review, and analyzed using Spradley’s ethnographic analysis model. The findings reveal that the buwuh tradition has shifted from a voluntary contribution to a practice resembling social debt, characterized by the recording of contribution amounts and expectations of reciprocity. This transformation produces dual socio-economic effects: it strengthens social ties and provides financial support, yet simultaneously imposes economic burdens on economically vulnerable groups. Social capital in the form of norms, trust, and social networks continues to sustain the existence of buwuh, but also exhibits an ambivalent nature by potentially generating social and economic pressure. The implications of this study highlight the need for managing social capital values to ensure the sustainability of the buwuh tradition without exacerbating socio-economic inequality.